Evaluating the Readiness Of Malaysian Academic University Libraries Towards Library 4.0 - Mohamad Sharif, Sabri; Hariro Samsudin, Ahmad Zam; Shafeera Amdan, Anum (International Journal of Interactive Mobile Technologies (iJIM), 2020)
This paper evaluates the readiness of Malaysian academic university libraries towards Library 4.0. The rise of this new intervention of Web 4.0 and Library 4.0 are being deliberated among librarians for future services. Information technology facilities have been identified and analysed which may comprehend the use of libraries for the next generation. This will also help to move the library forward and improve the overall performance of university libraries respectively. The methodology used for this study is qualitative. This qualitative study was piloted among librarians working in the selected academic university libraries. This study gives an outline of the readiness among the selected academic university libraries towards Library 4.0